Presenting Information Economics to Students. - Williamson, Robert W. (The Accounting Review, 1982)
ABSTRACT: The expected value of information is an important concept in cost and managerial accounting. Quite often students have difficulty integrating and applying statistical techniques to accounting problems. Contributing to this difficulty is the occasional lack of standardization of terms in the two disciplines. This article describes an approach which introduces information economics to managerial and cost accounting classes, Included is an Appendix which can serve as the basis for a classroom presentation by the instructor or which can be reproduced and distributed to students.